Assisted mechanical ventilation: the future is now! - Kacmarek, Robert M (BMC Anesthesiol, 2015)
Assisted ventilation is a highly complex process that requires an intimate interaction between the ventilator and the patient. The complexity of this form of ventilation is frequently underappreciated by the bedside clinician. In assisted mechanical ventilation, regardless of the specific mode, the ventilator’s gas delivery pattern and the patient’s breathing pattern must match near perfectly or asynchrony between the patient and the ventilator occurs. Asynchrony can be categorized into four general types: flow asynchrony; trigger asynchrony; cycle asynchrony; and mode asynchrony. In an article recently published in BMC Anesthesiology, Hodane et al. have demonstrated reduced asynchrony during assisted ventilation with Neurally Adjusted Ventilatory Assist (NAVA) as compared to pressure support ventilation (PSV). These findings add to the growing volume of data indicating that modes of ventilation that provide proportional assistance to ventilation – e.g., NAVA and Proportional Assist Ventilation (PAV) – markedly reduce asynchrony. As it becomes more accepted that the respiratory center of the patient in most circumstances is the most appropriate determinant of ventilatory pattern and as the negative outcome effects of patient-ventilator asynchrony become ever more recognized, we can expect NAVA and PAV to become the preferred modes of assisted ventilation!